How Educational Flipbooks and Learning Motivation Affect Early Reading Proficiency in First-Grade Kindergarteners - Ermaliana Khoirunnisak; Achmad Noor Fatirul; Harwanto (Universitas Veteran Bangun Nusantara, 2024)
Kindergarten provides early childhood education for children aged 0-6 years, aiming to develop their cognitive, social, and emotional skills through various educational approaches. This study examines the effect of using educational props, specifically flipbooks, and learning motivation on early reading skills in kindergarten children. A quasi-experimental method with a non-equivalent control group design was employed. The study involved two groups of kindergarten students: the experimental group, which used flipbooks, and the control group, which followed a conventional learning model. The results indicated that using flipbooks significantly improved early reading skills compared to the conventional method. Additionally, learning motivation was found to have a significant effect on reading ability. The interaction between using flipbooks and learning motivation demonstrated that their combination significantly enhanced children's reading ability. This study concludes that employing flipbooks and fostering students' learning motivation can improve the early reading skills of kindergarten children. Therefore, integrating flipbook and emphasizing learning motivation can have a significant and positive impact on early reading comprehension skills in kindergarten students, both individually and synergistically.